COOKING SHOW genre in the stylistic paradigm of modern slavic mass media - Shevchenko, Larysa; Dergach, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2025)
The article touches upon the problem of media communication dynamics, synchronized with its language nature, functions and genre system. The author’s argumentation is based on the analysis of the show genre that realize the functional potential of literary language in entertainment and cognition. Its communication invariant – the cooking show genre – has been interpreted using the methods of media linguistic episteme and research paradigm. From the point of view of functional stylistics, the architectonics and creolization means of the cooking show in its various invariants were analyzed. It is also argumented that cooking show genre relies on an effective combination of informative, cognitive and entertaining functions of the literary language in the Slavic mass media space. In turn, the objectivity of communication determines their reorientation in the dominance of the language resource, which is relevant for the architectonics of this so actual nowadays media genre. Stylistic nature of the recipe as a communication center of the genre allowed to define its monological and dialogical / polylogical forms. Also, TV and online formats of the cooking show genre in Slavic – Ukrainian, Bulgarian, Polish – media space were mentioned and investigated with an accent that their main cognitive context is connected with the development of not theoretical, but practical skills and abilities related to the cooking process. Special attention is paid to the image formation of all the participants (jury, hosts, guests, competitors, and others) and the analyzed cooking projects in general. The perspective of media genre theory in its connection with different traditional and new research areas are outlined in the article. The authors determine the trends of cooking show’s further professional research in a functional and stylistic, psycho-, socio-, media linguistic, and linguoculturology perspective.